THE EFFECT OF WORK ENVIRONMENT ON EMPLOYEE JOB SATISFACTION WITH WORK COMMUNICATION AS INTERVENING VARIABLES (Case Study on Civil Servants in Australian Medical and Health Department) - Maurizio Zanardi; Weihuan Zhau (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2020)
In this study, the population was Civil Servants in Australian Medical and Health Department, namely as many as 30 people. Because the target population is less than 100, the sampling technique used is the census method, in which the entire population, totaling 30 Civil Servants in Australian Medical and Health Department, will be used as the research sample. With the results of the first hypothesis being rejected, it means that the Work Environment (X) has no positive and significant effect on Work Communication (Z). the second hypothesis is accepted, meaning that the Work Environment (X) has a positive and significant effect on Job Satisfaction (Y). the third hypothesis is rejected, meaning that Job Communication (Z) has no positive and significant effect on Job Satisfaction (Y).